Civil society participation in REDD+ and FLEGT processes: Case study analysis from Cameroon, Ghana, Liberia and the Republic of Congo - Satyal, Poshendra (Forest policy and economics, 2018)
REDD+ (Reducing Emissions from Deforestation and Forest Degradation) and FLEGT (Forest Law Enforcement, Governance and Trade) are two initiatives with roots at an international scale that aim to influence national and local level forest governance. This paper looks to understand how the breadth and depth of participation of different types of actors, most particularly civil society, compares between these initiatives and in what ways the structure of the governance arrangement and/or the focus of commodities may influence this participation. The paper presents findings from an assessment study on the dynamics of participation of civil society actors in REDD+ and FLEGT processes in four countries of Central and Western Africa: Cameroon, Ghana, Liberia and the Republic of Congo. Building on key civil society participation literature, a questionnaire tool was developed and applied in these countries. The analysis is drawn from interviews based on the questionnaire tool, some in-depth interviews and secondary research. The study finds that there is a growing recognition of civil society participation in national policy making of forest governance in the four countries, and a majority of the civil society organisations are participating in REDD+ and FLEGT processes. The quality and degree of their participation (that can range from informing to empowering) however, varies between FLEGT and REDD+ (i.e. FLEGT being more accommodative than REDD+), among a diversity of these actors and the studied countries. The difference in participation between REDD+ and FLEGT is related to the design of these two processes, the general lack of time and financial investment and the technical nature of REDD+ consultations. Moreover, FLEGT has been more inclusive and participatory right from the beginning whereas participatory spaces are generally lacking in REDD+ process, most particularly in its initial stages. As REDD+ and FLEGT processes are being consolidated in these countries and worldwide, this paper provides several avenues of interventions needed to address gaps on participation, such as strengthening participatory platforms, addressing representation deficit for community groups and focusing on capacity building of civil society actors. •The paper compares and contrasts civil society participation in FLEGT and REDD+ in Central and Western Africa.•A questionnaire tool was developed and applied for assessment in Cameroon, Ghana, Liberia and Republic of Congo.•There are increasing instances of participation, but gaps remain between its utopian objective and implementation.•Difference in participation between FLEGT and REDD+ is due to the subject matter of consultations and commodity at stake.•It is also related to the design of these two processes and the general lack of time and financial investment in REDD+.•The paper discusses several issues that can enhance or constrain civil society participation and recommends key interventions.